2010
DOI: 10.1007/s10803-010-1140-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health-Related Quality of Life Among Primary Caregivers of Children with Autism Spectrum Disorders

Abstract: The impact of caring for a child with autism on caregivers' health-related quality of life (HRQOL) is not fully understood. The objective of this study was to compare the HRQOL scores of caregivers of children with autism to those of the general US population and to identify the factors that influence HRQOL. Caregivers of children with autism had lower HRQOL scores than the general population. Care recipient level of functional impairment, social support, use of maladaptive coping, and burden influenced caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
177
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(207 citation statements)
references
References 59 publications
(77 reference statements)
12
177
3
15
Order By: Relevance
“…Research has shown that caregivers of persons with ASD report depressive symptoms (Ekas et al, 2010 andFirth andDryer, 2013) and previous studies showed that parents of persons with ASD are at higher risk for developing depression than parents of normally developed children (Benson, 2006 andKhanna et al, 2011). On the other hand, research has shown that persons with ASD themselves may experience anxiety and depression (Almansour et al, 2013 andStrang et al, 2012), which can in turn elevate caregivers' depression.…”
mentioning
confidence: 99%
“…Research has shown that caregivers of persons with ASD report depressive symptoms (Ekas et al, 2010 andFirth andDryer, 2013) and previous studies showed that parents of persons with ASD are at higher risk for developing depression than parents of normally developed children (Benson, 2006 andKhanna et al, 2011). On the other hand, research has shown that persons with ASD themselves may experience anxiety and depression (Almansour et al, 2013 andStrang et al, 2012), which can in turn elevate caregivers' depression.…”
mentioning
confidence: 99%
“…These collective deficiencies oftentimes negatively impact the parents, resulting in deleterious health consequences, such as diminished maternal health related quality of life (HRQOL) (Allik, Larsson, & Smedje, 2006) or increased problems in physical health and reported bodily pain (Khanna et al, 2011). In comparison to parents of typically functioning children or parents of children with other developmental disabilities (i.e.…”
mentioning
confidence: 99%
“…For Step 1 in order to define the construct and the domains to be included in the outcome measure the developmental milestones for the pre-school age group that were commonly delayed in children with ASD were determined from the literature 19,35,[37][38][39] . The type of items and layout of international outcome measures were also reviewed 26,27,29,40 .…”
Section: Research Proceduresmentioning
confidence: 99%